Ruta Agroturística del Barrio Pitá, del Cantón Yantzaza, Provincia de Zamora Chinchipe - Calva Delgado, Viviana Lizeth (2019)
Agrotourism has allowed countries to strengthen the existing activities of their peoples, taking advantage of and enjoying the environment, natural, cultural and socio-productive values that allow the interaction of the tourist with the community. Ecuador is a country known for its mega diversity both culturally and in its flora and faúna because of this the protection of these elements has been consolidated since they are the essential representation of the country. In recent years, Ecuador has been improving its infrastructure and offer of tourist services; to meet the travel expectations of tourists who currently prefer to perform activities that allow them to have a closeness with local communities and nature. Consequently, to meet the needs of tourism demand has resorted to the development of new products such as routes in places where you can experience the agrotourism, allowing you to know different places and traditions of each area visited with the enjoyment of displacement. Every meter and every stop. To the East is the Province of Zamora Chinchipe that contains the canton Yantzaza which is a pioneer in agricultural and livestock activities throughout the province, as well as possess natural, cultural, scenic, flora and faúna resources that are taken advantage of tourism. In the cantonal canton of Yantzaza is the same Pitá neighborhood that has the largest production of sugar cane resulting in the production of panela and other derivatives of this plant. What makes this neighborhood special is the amount of milling that is found around the perimeter and agricultural and livestock activities that are practiced in them. This is how an opportunity for economic development was determined in the Barrio Pitá, considering one of the capos of tourism directly related to agriculture, becoming known as agrotourism, integrating the farms with attractions of the cantonal head and for this it is convenient to develop the 6 research work , for the realization of the same one general objective was raised: "To design a proposal of an Agrotourism route in the Pitá District, of the Canton Yantzaza, Province of Zamora Chinchipe". For the fulfillment of the general objective, three specific objectives were considered: the first objective To carry out the Tourist Diagnosis of the cantonal canton of Yantzaza, province of Zamora Chinchipe "; for the development of the objective it was used: analytical, synthetic and inductive method; also the techniques of direct observation and interview; tourist diagnostic manual of Carla Ricaurte communities, bibliographic sources, hierarchical index cards of the tourism ministry, SWOT matrix and strategies from which the current situation of the cantonal capital was known. In the second objective: Propose a model of Agrotourism Route in the Pita neighborhood of the canton Yantzaza province of Zamora Chinchipe; In order to comply with the objective, the deductive method was used, as well as fieldwork that allowed to know the attractions and activities that have been included in the proposal. Subsequently, marketing strategies were established in order to identify and promote the tourist product. In addition, the design of the pictograms and signs was carried out through the signage manual of the Ministry of Tourism. The third objective is to "Socialize the Design of the Agrotourism Route to the stakeholders involved in the Pitá neighborhood of the canton of Yantzaza province of Zamora Chinchipe"; for the fulfillment of the last objective the method of rapid analysis and participatory planning (MARPP) was used, which comprises three phases: First phase, consisted in sending personal communications and invitations to the authorities and actors involved; Second phase, the development of socialization was carried out in the presence of the actors involved through audiovisual material; Third phase: the questions, suggestions and recommendations were opened by the attendees. 7 As a result, the cantonal capital of Yantzaza to which the Pitá neighborhood belongs have an offer of services, infrastructure, natural resources and cultural manifestation suitable for the realization of the Agrotourism route, which will contribute to the tourist strengthening of the Canton especially in the agricultural area, waiting for a local economic development. It is recommended that the authorities of the Cantonal Gad, together with the Tourism Unit, consider the Agrotourism route as a means of economic development based on the agricultural activities of the Pitá neighborhood farms in order to stimulate this activity.